Role of Organizational Flexibility in Enhancing Sustainable Green Management Practices: A Study in Emerging Market Context (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Purpose The purpose of this paper is to identify the variables influencing the role of organizational flexibility in enhancing sustainable organization (SO) by adopting green management practices. The empirical research study identifies the characteristics of internal environment to enhance sustainable green management practices in firmsoperating in an emerging economy, such as India. Design/methodology/approach The authors studied a sample size of 62 firms all over India and measured the internal environment for enhancing sustainable green management practices. In total, 142 responses were collected.Using SPSS tool, the authors measured the impact of these variables on sustainable outcomes.Findings It was found that the critical variables with respect to Indian context included management support, a nd organizational flexibility for developing environmentally sustainable organization.Research limitations/implications Further confirmatory research needs to be conducted to establish the stability of these factors. The results need to be tested on a larger sample size. Moreover, the tool developed needs to be tested for other emerging economy context too for generalization. Practical implications Organizational flexibility would enhance the sustainable capability of the companies to compete by enhancing their competitiveness in emerging economies by adopting green management practices. Therefore, it would be critical to study the role of green management practices in enhancing the sustainability and competitiveness of the firms operating in the Indian economy. Originality/value Earlier studies have not included two important parameters, including role of organizational flexibility and management support as drivers of sustainable development even in the developed country context. Moreover, the influence of organizational flexibility on green management practices needs to be studied in the context of sustainable development which was missing in the earlier literature.